An Innovative Process for Ultra‐Thick Electrodes Elaboration: Toward Low‐Cost and High‐Energy Batteries. Issue 5 (12th April 2019) - Zolin, Lorenzo; Chandesris, Marion; Porcher, Willy; Lestriez, Bernard
Abstract : An effective route to enhance the volume ratio of active materials in a lithium‐ion battery (LIB) or sodium‐ion battery (NaB) consists in increasing the electrode thickness, that is, active mass loading, as it reduces the volume and weight fractions of the separator and current collectors in the cell. This approach also serves to reduce the battery cost, chiefly associated with the expensive polymeric separator. However, following the standard industrial coating process, the mechanically stable electrode can hardly exceed an active mass loading of about 30 mg cm −2, corresponding to a nominal areal capacity around 6 mAh cm −2 due to the binder migration during the drying step. Herein, a straightforward manufacturing process based on a filtration technique is developed. It enables the design of LIB electrodes with a nominal areal capacity up to 20 mAh cm −2 . A pierced and serrated current collector allows at the same time both filtration and mechanical interlocking of the electrode layer. Cells assembled with such ultra‐thick filtered electrodes exhibit very promising performances, thereby promoting the design of high‐energy and low‐cost LIBs and NaBs by a fast fabrication process. Abstract : A straightforward manufacturing process based on a filtration technique enables the design of electrodes with a nominal areal capacity up to 20 mAh cm −2 and reduces the separator and current collector fraction in the cell. Both filtration and mechanical interlocking of the electrode layer are achieved at the same time with a pierced and serrated current collector.